2015
DOI: 10.1098/rstb.2014.0177
|View full text |Cite
|
Sign up to set email alerts
|

Peto's paradox and the promise of comparative oncology

Abstract: One contribution of 18 to a theme issue 'Cancer across life: Peto's paradox and the promise of comparative oncology'.Subject Areas: evolution, health and disease and epidemiology, molecular biology, physiology Keywords:Peto's paradox, comparative oncology, evolution, life-history theory, cancer, modelling The past several decades have seen a paradigm shift with the integration of evolutionary thinking into studying cancer. The evolutionary lens is most commonly employed in understanding cancer emergence, tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 60 publications
1
60
0
Order By: Relevance
“…Recent syntheses propose that telomere length of vertebrates may be under stabilizing selection by functioning as an anti-cancer mechanism (Aviv et al 2017;Young 2018). This hypothesis is primarily based on the observation that larger vertebrates with long periods of growth tend to have shorter telomeres than small vertebrates and the premise that this relationship coexists with a higher cancer risk in larger species, but see (Nunney et al 2015). Shorter telomere length could be adaptive in large vertebrates when it selectively shuts down cell proliferation of unstable cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent syntheses propose that telomere length of vertebrates may be under stabilizing selection by functioning as an anti-cancer mechanism (Aviv et al 2017;Young 2018). This hypothesis is primarily based on the observation that larger vertebrates with long periods of growth tend to have shorter telomeres than small vertebrates and the premise that this relationship coexists with a higher cancer risk in larger species, but see (Nunney et al 2015). Shorter telomere length could be adaptive in large vertebrates when it selectively shuts down cell proliferation of unstable cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given that replications of somatic cells increase the organismal mutation burden and hence cancer risk, Peto reasoned four decades ago that large mammals should have more cancer than small ones, yet there is no evidence that cancer risk scales with body size [17]. Large mammals, who are by and large long-living [18], have developed an array of anti-cancer defenses, a few of which might be unique for a given species, while others are shared across species.…”
Section: Evolutionary and Epidemiological Perspectivesmentioning
confidence: 99%
“…Indeed, if every cell has some chance of becoming cancerous, large long‐lived organisms should have an increased risk of developing cancer compared to small, short‐lived organisms. The lack of correlation therewith suggests that the mechanisms of cancer resistance must have been more strongly selected in large and long‐lived species (Caulin & Maley, ; Nunney, Maley, Breen, Hochberg, & Schiffman, ; Roche et al., ). Accordingly, it has for instance been shown that large vertebrates such as elephants have 20 copies of TP53 (humans have only one), horses seem to have larger number of T‐cell differentiation protein (MAL) genes, and bats (that live unexpectedly long given their small body size) have amplified F‐box protein 31 (FBXO31) (Caulin, Graham, Wang, & Maley, ; Harris, Schiffman, & Boddy, ; Kokko, Schindler, & Sprouffske, ).…”
Section: Introductionmentioning
confidence: 99%